(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The present study aims to analyze the reintegration of adolescents with cancer in the schools of origin in Romania using the preparation scale for the reintegration of adolescents with cancer, which has 8 sub-scales and 71 items after the adolescents have completed the hospital school courses. It was necessary to use this scale because in Romania there is no reintegration scale for adolescents with long hospitalization experience. In June 2023, through a survey, 36 teenagers (15 girls, 21 boys), who lived a long-term experience in a hospital, answered the 71 items of the reintegration preparation scale (RRS) of pediatric oncology in Bucharest Romania, who were students in the hospital school and returned to the school of origin. The scale contains 8 subscales, namely: Self-management of behavior (10 items), Relationships between the student and others (10 items), Self-awareness (5 items), Self-confidence (5 items), Self-organization (12 items), Attitude (10 items ), Learning Skills (11 items), Reading Skills (8 items).The study emphasizes the importance of using the reintegration preparation scale (RRS) for adolescent patients in Romania, the results obtained being able to make the interventions of the psycho-educational reintegration team of adolescents with cancer more efficient.